Role of early postnatal aEEG and brain MRI in predicting neurodevelopmental outcome in preterm infants at the age of 1 year - Eman Mahmoud Metwalli; Iman Khaled Eyada; Walaa Alsharany Abuelhamd; Hadeel Mohamed Seif; Heba Samy Ibrahim Hammad; Yara Salah Aly Shaheen (SpringerOpen, 2024)
Abstract Background Preterm birth is a principal reason for perinatal morbidity and mortality increasing the incidence of severe neurodevelopmental deficits. There is growing proof that early postnatal amplitude-integrated electroencephalography (aEEG) has a prognostic value for neurodevelopmental consequence in preterm born neonates. Furthermore, MRI has been widely utilized to enhance comprehension of the brain substrate responsible for neurodevelopmental abnormalities. Thus, this study aims at evaluating the role of early postnatal aEEG and brain MRI in forecasting neurodevelopmental consequence in preterm infants at the age of 1 year. Methods A cohort study performed in the neonatal intensive care unit of a tertiary hospital during the duration from October 2021 to June 2023 including 60 preterm neonates < 32 weeks of gestation. All cases were monitored by aEEG within the 1st 72 h of life for at least 4 h, and then brain MRI and aEEG were done at term equivalent age (TEA) of 40 weeks. Regarding the neurodevelopmental outcome, our cases were assessed by Bayley scale III screening test at the age of 1 year. Results Of the study participants, 41.7% were males, and 58.3% were females with a mean gestational age of 30.40 ± 0.94 weeks and mean weight of 1.36 ± 0.17 kg. aEEG showed that 83.3% of the cases had continuous normal background activity at TEA, and MRI showed that 75% of the cases were normal. Comparing between non-affected and affected groups as categorized by Bayley scale regarding aEEG and MRI findings, there was greatly statistically significant difference between the two groups (P < 0.001). Brain MRI showed higher sensitivity and accuracy than aEEG. Conclusion Brain MRI at TEA is more sensitive and accurate than aEEG to predict the neurodevelopmental outcome. aEEG at TEA is more predictor for neurodevelopmental outcome than at birth. The combination of both aEEG and brain MRI at TEA gives more prediction about the degree of affection in neurodevelopmental outcome in preterm infants.